The Relationship Between Driver Behaviour Towards Speeding in Muar - Nur Hazreen Abdul Wahab; Nurul Anisah Kasran; Siti Nur Hidayah Roslan; Nur’Ain Idris (Multidisciplinary Applied Research and Innovation, 2022)
Driver behaviour is often related to vehicle speed which can result in road accidents in Muar. Vehicle speed may vary in time depending on the external or internal factors which might affecting the driver. Several external and internal factors of the driver such as driving experience, emotional factors and the driver’s knowledge of the speed limit need to be examined in order to have the connection between the driver’s attitude and speed. This is because, driving speed is an important component in driving behaviour on the road and has an influence in the frequency and severity of accidents. The main objective of this study is to evaluate the drivers’ behaviour and it should be understood to identify the cause of a road accident. Site observations and questionnaires survey methods were conducted to gather all the information required for this study. Site observations conducted around Muar are to see for themselves the attitude of drivers towards their speed when driving in the Muar area. In addition, questionnaires were distributed to residents around Muar to assess their attitude and driving. The results of the study have successfully proved the objective to assess the relationship between driver behavior on speed in Muar. It can be concluded that this study has achieved its objective to identify the attitudes of driver in order to reduce the number of accidents in Muar. However, there are still some improvements and enhancements that need to be considered in terms of questionnaires such as the question of the involvement of respondents to accidents in Muar.